Neck shape optimization of resonator-type sound absorbers using adjoint lattice Boltzmann method - Kimiya Takeuchi; Kazuya Kusano (AIP Advances)
Resonant sound-absorbing devices, such as Helmholtz resonators, can effectively reduce discrete frequency noise radiated from various engineering equipment. In this study, we attempted to improve the sound absorption characteristics of a Helmholtz resonator using an unsteady adjoint method based on the lattice Boltzmann equation. The adjoint-based shape optimization created a concave shape on the upper side and a convex shape on the lower side of the resonator neck, alleviating noise to a greater extent compared with straight and serrated neck shapes. Furthermore, the fluid simulation results revealed that the optimization process did not alter the resonant frequency. A visualization of the energy dissipation function indicated that the presence of the convex region in the optimized shape helped increase the local velocity gradient in the neck region, thereby enhancing viscous dissipation and improving absorption performance. The concave region was suggested to play a role in preserving the resonant frequency by compensating for the creation of the convex region, aligning the natural frequency of the resonator with that of the sound source. Our findings can aid in the design of sound-absorbing devices.